(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Pneumatosis Cystoides Intestinalis is a rare condition characterised by gas-filled cysts in the wall of the smallgut and sometimes in its mesentry. When the process is limited to the large intestine, the term pneumatosis coli is used . The exact cause of the condition is unknown but it may develop in diseases like peptic ulcer, ulcerative colitis, regional enteritis, chronic bronchitis etc. The condition is usually diagnosed incidentally during abdominal scanning or investigation for the primary disease. Presentation as a case of gastric outlet obstruction (proximal jejunal obstruction) as happened in this case, is rare. A young adult male cultivator presented as a case of gastric outlet obstruction due to suspected chronic duodenal ulcer ( a common complication of Peptic ulcer disease in our country ). Per-operatively, gas filled cysts in proximal jejunum with almost obliteration of the lumen of the intestine was detected and diagnosed as a case of pneumatosis cystoides intestinalis and was treated with resection and anastomosis of the affected portion of gut. The patient is in good health even 5 years after the operation and showed no signs of recurrence of the condition. DOI: 10.3329/jbcps.v27i1.4243 J Bangladesh Coll Phys Surg 2009; 27: 45-48